2011
DOI: 10.1097/ccm.0b013e318205c7bc
|View full text |Cite
|
Sign up to set email alerts
|

Effect of transcutaneous electrical muscle stimulation on muscle volume in patients with septic shock*

Abstract: We observed a marked decrease in quadriceps volume within the first week of intensive care for septic shock. This loss of muscle mass was unaffected by transcutaneous electrical muscle stimulation applied for 60 mins per day for 7 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
169
2
20

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(195 citation statements)
references
References 50 publications
4
169
2
20
Order By: Relevance
“…Preliminary results in small samples of critically ill patients were promising and found that EMS preserved muscle mass (237,272,474), reduced muscle catabolism (73), and exerted shortterm systemic microcirculatory effects (238). In another eight patients with septic shock however, 7 days of EMS did not preserve muscle volume (555). Several randomized studies examining the effects of EMS on muscle function in the ICU recently emerged.…”
Section: Electrical Muscle Stimulationmentioning
confidence: 97%
“…Preliminary results in small samples of critically ill patients were promising and found that EMS preserved muscle mass (237,272,474), reduced muscle catabolism (73), and exerted shortterm systemic microcirculatory effects (238). In another eight patients with septic shock however, 7 days of EMS did not preserve muscle volume (555). Several randomized studies examining the effects of EMS on muscle function in the ICU recently emerged.…”
Section: Electrical Muscle Stimulationmentioning
confidence: 97%
“…Muscle strength and muscle protein synthesis were improved more on Physical Disabilities -Therapeutic Implicationsthe stimulated side limb, although the muscle cross-sectional area and muscle mass decreased in both limbs [125,126]. A previous RCT using NMES indicated increased muscle strength and decreased mechanical ventilator duration and the incidence of ICUAW decreased from 39.3 to 12.5% in the NMES intervention group [127].…”
Section: Neuromuscular Electrical Stimulationmentioning
confidence: 99%
“…J. Poulsen и соавт. [32] в 2011 г. в исследовании со схожим дизайном показали, что у 8 пациентов с септическим шоком 7-дневный курс ЭСМ не оказывает влияния на количество мышечной ткани. У пациентов произошла атрофия мышц как на стороне стимуляции, так и на противоположной.…”
Section: клинические данные использования эсм в оритunclassified